PENGENDALIAN PENGADAAN BARANG PT PERTAMINA HULU ENERGI OFFSHORE NORTH WEST JAVA - Peppy Fachrial; Cynthia Arum Pradhani; Adenan Suhalis (Institut Transportasi dan Logistik Trisakti, 2018)
The purpose of this study is to analyze the implementation of e-procurement as the effort of controlling the utilities procurement at PT Pertamina Hulu Energi ONWJ Jakarta. The method of this study is descriptive quantitative with the statistics descriptive and Model Product Moment (correlation coefficient) with 11 respondents as the sample used as the tools of the analysis. The result of the study shows correlation coefficient of 0.7215 which means there is a strong integration of the implementation of e-procurement as the effort of controlling the utilities procurement at PT Pertamina Hulu Energi ONWJ Jakarta.